Strategies cooperation on designing nickel catalysts to access ultrahigh molecular weight polyethylenes. (1st February 2022) - Xia, Jian; Kou, Shuqing; Zhang, Yixin; Jian, Zhongbao
Abstract: To address the issue of polymer molecular weight in olefin polymerization, versatile strategies have been utilized in the benchmark α-diimine nickel catalysts. In this contribution, one cooperative strategy that combines the concerted double-layer steric strategy with the rotation-restricted strategy was highlighted in the newly prepared α-diimine nickel catalysts. By using this strategy, these nickel catalysts with the flexible restraint and the rigid restraint exhibited enhanced molecular weight than the freely rotated one in ethylene polymerization. More strikingly, the preferred nickel catalyst had the ability to produce virtually linear polyethylene (0.8 brs/1000C, T m  = 130.2 °C) with both ultrahigh molecular weight of 7097 kg mol −1 and ultrahigh catalytic activity. Even at high temperature of 90 °C, an ultrahigh molecular weight of 1103 kg mol −1 was accessible. Graphical abstract: Image 1 Highlights: A cooperative strategy of combining concerted double-layer steric strategy and rotation-restricted strategy. Flexible and rigid restraints of freely rotated phenyl rings enhanced molecular weight. Preferred Ni catalyst enabled ultrahigh molecular weight polyethylene in ultrahigh activity. Virtually linear UHMWPE (7097 kg mol −1, 0.8 brs/1000C, T m  = 130.2 °C) was possible.